The Social Condition of England during 1800-1900 Reflected in “Song to the Man of England” and “England in 1819” by Percy B. Shelley. - Qurrota Aâ€™yun, Annisa (LANTERN (Journal on English Language, Culture and Literature), 2016)
In this thesis, the writer combines the analysis of the two poems written by Percy B. Shelley entitled “Song to the Man of England” and “England in 1819”. The writer analyzes these two poems with the same poet, Percy B. Shelley, because both of the poems are showing the condition of England people in that era. The purposes for the writer to write this thesis are to analyze the intrinsic elements, which is imageries, metaphor, and diction that is reflected in these two poems. The other purpose is to analyze the extrinsic element of the two poems and the condition of people in England during the Romantic Period (1811-1820), which is represented from the two poems in which the writer uses sociological approach and Marxist theory. The research method that the writer uses is contextual research method in which the writer analyzes the intrinsic element and the extrinsic elements of the poems. The results after analyzing these two poems is the writer can analyze the condition of people in England during the year 1800-1900 that is represented in these two poems.In this thesis, the writer combines the analysis of the two poems written by Percy B. Shelley entitled “Song to the Man of England” and “England in 1819”. The writer analyzes these two poems with the same poet, Percy B. Shelley, because both of the poems are showing the condition of England people in that era. The purposes for the writer to write this thesis are to analyze the intrinsic elements, which is imageries, metaphor, and diction that is reflected in these two poems. The other purpose is to analyze the extrinsic element of the two poems and the condition of people in England during the Romantic Period (1811-1820), which is represented from the two poems in which the writer uses sociological approach and Marxist theory. The research method that the writer uses is contextual research method in which the writer analyzes the intrinsic element and the extrinsic elements of the poems. The results after analyzing these two poems is the writer can analyze the condition of people in England during the year 1800-1900 that is represented in these two poems.